A Study of the Electrodynamic Properties of Macroscopically Extended Fermion Matter - Kechriniotis, A.; Syros, C. (HNPS Advances in Nuclear Physics, 2020)
Finite!y extended fermion matter is studied inthe framework of Dirac's theory. Some asnaiytic properties of the spinors are discussed. Propositions are demonstrated important for the formulation of the solution.